Examining Differences in Utilization of the Ontario eConsult Service in Rural Versus Urban Settings: A Retrospective Cross-Sectional Analysis - Clare Liddy; Sheena Guglani; Nikhat Nawar; Erin Keely (Journal of Primary Care & Community Health)
Introduction: We conducted a retrospective, cross-sectional analysis exploring patterns of usage and outcomes from urban vs. rural eConsults to examine eConsult’s impact on equity of access in rural Ontario, Canada. Patients living in rural regions face many barriers in accessing specialist care. The Ontario eConsult Service connects primary care providers (PCP) with specialists regardless of geographical location, improving equity of access. Methods: We included all Ontario eConsult cases submitted between January 1 and December 31, 2021. Usage data collected automatically by the service and responses to a mandatory closeout survey were analyzed using descriptive statistics. Cases were identified as rural using the forward sorting area of the PCP’s primary practice. Results: Of the 72,948 cases submitted during the study period, 7550 were coded rural. Usage among rural PCPs was most frequent in Ontario Health North East (1.78 eConsult cases/1000 residents) and Ontario Health North West (1.64). Rural and urban eConsult cases had the same top 5 most frequently requested specialties. Both groups had median response times of 1.0 days, reported time billed of 15 min, and cost per case of $50. Conclusions: PCPs in rural and urban regions use eConsult with equal frequency and had similar usage patterns and outcomes.